Towards Identification of the Substrates of ATP-Binding Cassette Transporters - Lefèvre, François (Plant Physiol, 2018)
Most ATP-binding cassette (ABC) proteins function in transmembrane transport, and plant genomes encode a large number of ABC transporters compared with animal or fungal genomes. These transporters have been classified into eight subfamilies according to their topology and phylogenetic relationships. Transgenic plants and mutants with altered ABC transporter expression or function have contributed to deciphering the physiological roles of these proteins, such as in plant development, responses to biotic and abiotic stress, or detoxification activities within the cell. In agreement with the diversity of these functions, a large range of substrates (e.g. hormones and primary and secondary metabolites) have been identified. We review in detail transporters for which substrates have been unambiguously identified. However, some cases are far from clear, because some ABC transporters have the ability to transport several structurally unrelated substrates or because the identification of their substrates was performed indirectly without any flux measurement. Various heterologous or homologous expression systems have been used to better characterize the transport activity and other biochemical properties of ABC transporters, opening the way to addressing new issues such as the particular structural features of plant ABC transporters, the bidirectionality of transport, or the role of posttranslational modifications.